International perspectives on developing pedagogy towards the construction of Peace in Colombia (Quaestiones Disputatae: temas en debate, 2016)
This article seeks to propose proven examples from pedagogy in the international sphere that can help the development of pedagogy for peace in Colombia in light of a complex attitude towards peace among the general public. The article will argue that only a Critical pedagogy, as first framed by Paulo Freire, can be truly effective in addressing the multi-faceted reasons for the armed conflict in Colombia towards building a sustainably peaceful future. Cases of pedagogy from Northern Ireland and South Africa will be discussed along with the possibilities offered by pedagogies of nonviolence, restorative justice and economic justice as to how they can help the practice of teaching and learning directed toward personal, social, political and institutional change and transformation. The article will argue that such approaches to pedagogy when adapted to the Colombian situation have the potential to bring about real reconciliation and a commitment to justice in the economic, political and social lives of all Colombians.
Keywords: nonviolence; pedagogy for peace; reconciliation; restorative justice